Analysis of retinal function using chromatic pupillography in retinitis pigmentosa and the relationship to electrically evoked phosphene thresholds. Issue 4 (29th September 2016) - Kelbsch, Carina; Maeda, Fumiatsu; Lisowska, Jolanta; Lisowski, Lukasz; Strasser, Torsten; Stingl, Krunoslav; Wilhelm, Barbara; Wilhelm, Helmut; Peters, Tobias
Abstract: Purpose: To analyse pupil responses to specific chromatic stimuli in patients with advanced retinitis pigmentosa (RP) to ascertain whether chromatic pupillography can be used as an objective marker for residual retinal function. To examine correlations between parameters of the pupil response and the perception threshold of electrically evoked phosphenes. Methods: Chromatic pupillography was performed in 40 patients with advanced RP (visual acuity < 0.02 or visual field ≤5°, non‐recordable ERGs) and 40 age‐matched healthy subjects. Pupil responses to full‐field red (605 nm) and blue (420 nm) stimuli of 28 lx corneal illumination were recorded and analysed for two stimulus durations (1 and 4 seconds). The perception threshold of phosphenes to transcorneal electrostimulation was ascertained and correlated to the pupil responses and visual acuity. Results: Patients with RP showed significantly reduced pupil responses to red and blue stimuli compared with the controls. With red stimuli, pupillary escape could be observed; blue stimuli resulted in a well‐preserved postillumination pupil response. Phosphene thresholds were significantly increased in patients with RP and correlated with the parameters of the pupil response if all subjects were considered. Within the RP group alone, this relationship was less pronounced and statistically not significant. Conclusions: Chromatic pupillography demonstrated a significant decrease in outer retinal photoreceptor responses but a persisting and disinhibited intrinsic photosensitive retinal ganglion cell function in advanced RP. These phenomena may be useful as an objective marker for the efficacy of any interventional treatment for hereditary retinal diseases as well as for the selection of suitable patients for an electronic retinal implant.